Dual antiplatelet therapy in patients with diabetes mellitus: special considerations. (March 2013) - Capranzano, Piera; Capodanno, Davide
Diabetes mellitus (DM) is associated with higher rates of ischemic events in patients suffering from an acute coronary syndrome and/or undergoing percutaneous coronary intervention, thereby underscoring the need to develop more effective and specific strategies toward mitigation of the cardiovascular burden associated with DM. Platelet hyper-reactivity associated with DM is a central contributor to this high risk, since platelets are the key players in the processes underpinning atherothrombotic complications, thereby representing a specific therapeutic target. Oral dual antiplatelet therapy comprising the combination of aspirin (75–100 mg) and clopidogrel (75 mg) has been, for years, the standard antithrombotic treatment for patients with acute coronary syndrome and/or undergoing percutaneous coronary intervention. However, despite the use of this therapy, high rates of cardiovascular events continue to occur, especially within the cohort of patients with DM. These observations could be in part explained by an inadequate clopidogrel-induced platelet inhibition, which has been associated with impaired clinical outcomes. In particular, DM is associated with a higher prevalence of reduced responsiveness to standard dual antiplatelet therapy, which may contribute to the higher rates of ischemic events seen in this population. These findings have prompted the identification of alternative dual antiplatelet treatment regimens to optimize platelet inhibition. The present review aims to describe benefits and limitations of oral dual antiplatelet therapy with aspirin and clopidogrel (75 mg) and to appraise the evidence regarding alternative oral dual antiplatelet therapy regimens, which include higher doses of aspirin and clopidogrel or the combination of prasugrel or ticagrelor with aspirin, focusing on patients with DM.